A dynamic simulation model for digestion, gut transit, and absorption in the ballan wrasse, Labrus bergylta - T.S. Silva; L.E.C. Conceição; Ø. Sæle; I. Rønnestad (Aquaculture Reports)
Ballan wrasse is a widely used cleaner fish for farming Atlantic salmon and is collected from nature and reared for this purpose. One of the main bottlenecks in ballan wrasse rearing is formulation of diets that result in high feed intake, growth, and health. The problem is believed to be related to poor acceptability of diets and functional properties of the agastric, short digestive system of the species. The aim of this study was to improve understanding of digestive functions as basis for making better feed and improving overall production performance.For this purpose, we developed a mechanistic dynamic model that quantifies digestion, absorption, and retention efficiency of selected macronutrients in ballan wrasse. Dynamic models are powerful tools for integrating practical data from experiments with hypotheses, theoretical concepts, and literature data in an iterative process that clarifies and controls experiments, hypotheses, and designs. Due to its mechanical nature, the ballan wrasse model can be easily adapted to other fish species.The model was calibrated with previously published results where the fish were fed diets with added inert markers to follow digestion, absorption, and evacuation rate. The model overestimated protein digestibility/absorption (Apparent Digestibility Coefficient; ADC) in the first intestinal segment (S1) but showed good compliance for the rest of the intestine. Both the model and experimental data showed that a large fraction of protein absorption ADC-P was in S1. For lipids, both S2 and S3 contributed more to ADC-L. The gut transit time was calculated after feed change and was 12–14 h. It took 4–8 h for 90 % of the feed to move from S1 to midgut (S2). At this time, 7 % of the intestinal contents had entered the hindgut (S4). The model simulates transit of S4 well, but underestimates transfer rate from bulb (S1) to anterior midgut (S2).